Conteúdos ofensivos e métodos de ensino do handebol em ambiente escolar: perspectiva a partir da opinião de treinadores - Menezes, Rafael Pombo (2020)
The aim of this work was to analyze the opinion of school team handball coaches about the offensive content and the teaching approaches used by them. Semi-structured interviews were conducted with eleven coaches, whose statements were analyzed based on the Collective Subject Discourse Method. The main individual contents referred to as a) the good execution of the technique and the tactical elements; and b) the organizational evolution of the game. To teach these contents, the coaches mostly use the technique approach. The collective contents identified were: a) spatial orientation and environmental observation; and b) the execution of pre-established games, for which the coaches prefer to teach by the technique approach and through game situations. It is concluded that the use of the technique approach to teach individual and collective content limits the decision-making ability of players, and that the increased use of other approaches promotes a different understanding of the logic of the game. These aspects constitute a major point of tension because these coaches work within the school context.